Description of a New Labyrinthine Dehiscence: Horizontal Semicircular Canal Dehiscence at the Tympanic Segment of the Facial Nerve - Gianoli, Gerard; Soileau, James; Shore, Bradley (Frontiers in Neurology, 2022)
Objective: This is a case series of patients with findings suspicious for a labyrinthine dehiscence syndrome not previously described in the medical literature. We report 16 patients with CT findings suspicious for dehiscence of the ampullated end of the horizontal semicircular canal at the tympanic segment of the facial nerve. Interventions: Retrospective record review of patient symptoms, physical findings, audiometry, vestibular testing, and CT scans was performed. CT findings of other dehiscent sites were noted. Main outcome measures: History and physical exam were reviewed. Audiometry and vestibular testing were reviewed to determine which tests were most likely to be abnormal. CT scans were independently graded according to degree of suspicion for HSC-FND. Finally, patients with HSC-FND as the sole dehiscence identified were compared to those who had HSC-FND plus other dehiscent sites (HSC-FND+O). Results: 16 met inclusion criteria. Nine (56%) of those suspicious for HSC-FND had dehiscences in other parts of the labyrinth. Additional dehiscent sites included: six superior semicircular canal dehiscences (SSCD), two cochlear facial dehiscences and one cochlear carotid dehiscence. The most common auditory symptoms were autophony followed by tinnitus and aural fullness. The most common vestibular symptoms were pulsion sensation (feeling of being pushed to one side) followed by vertigo spells. The most common exacerbating factors for vertigo were straining, and sound. The most commonly abnormal vestibular test was nasal Valsalva testing, which was positive in all but one patient. Of note, cVEMP was more often found to have lower thresholds in the HSC-FND group compared to the HSC-FND+O group. An example case is highlighted. Conclusions: A new labyrinthine dehiscence has been described to occur where the tympanic segment of the facial nerve crosses over the ampullated end of the horizontal semicircular canal. HSC-FND patients can present in a similar manner as HSC-FND+O patients with similar test findings except as mentioned above. The identification of one dehiscence such as SSCD does not preclude the presence of another dehiscence such as HSC-FND. HSC-FND could be the source of persistent symptoms post SSCD surgery as illustrated in the case presented.